RISK ANALYSIS OF BROILER CHICKEN PRODUCTION IN CLOSED HOUSE SYSTEM FARMS WITH PARTNERSHIP PATTERNS IN SEMARANG CITY - Alfi Nur Fauzan; Willudjeng Roessali; Teysar Adi Sarjana (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to analyze the expected income and the level of the coefficient of variance. Risk status as seen from the risk source's probability and impact (Value at Risk). It provides alternative strategies to handle the risk of broiler rearing business in the closed house system of the Faculty of Agriculture and Animal Husbandry, Diponegoro University. The analytical method used calculates expected income, variance, standard deviation, coefficient of variation, probability, and impact of production risk sources. The results showed that the due payment of the cage was Rp153,359,387.7 per period with a coefficient of variation level of 0.55. The mortality of broiler chickens is caused by the risk of climate change and disease. Sources of climate change risk have a risk probability level of 45.2%, and sources of disease risk of 40.3%, with each impact of Rp.7,268,931.2 for climate change and disease of Rp 2,799,263.1. An alternative strategy in dealing with heads of climate change and disease risk is using a preventive strategy method.